1996
DOI: 10.1073/pnas.93.2.705
|View full text |Cite
|
Sign up to set email alerts
|

Male fetal progenitor cells persist in maternal blood for as long as 27 years postpartum.

Abstract: Rare nucleated fetal cells circulate within maternal blood. Noninvasive prenatal diagnosis by isolation and genetic analysis of these cells is currently being undertaken. We sought to determine if genetic evidence existed for persistent circulation of fetal cells from prior pregnancies. Venous blood samples were obtained from 32 pregnant women and 8 nonpregnant women who had given birth to males 6 months to 27 years earlier. Mononuclear cells were sorted by flow cytometry using antibodies to CD antigens 3, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
788
0
31

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,154 publications
(849 citation statements)
references
References 13 publications
20
788
0
31
Order By: Relevance
“…It was first identified in the early 1970s -but the big surprise came more than two decades later, when researchers discovered how long these crossover cells survive, even though they are foreign tissue that the body should, in theory, reject. A study in 1996 recorded women with fetal cells in their blood as many as 27 years after giving birth 13 ; another found that maternal cells remain in children up to adulthood 14 . This type of work has further blurred the sex divide, because it means that men often carry cells from their mothers, and women who have been pregnant with a male fetus can carry a smattering of its discarded cells.…”
Section: Cellular Sexmentioning
confidence: 99%
“…It was first identified in the early 1970s -but the big surprise came more than two decades later, when researchers discovered how long these crossover cells survive, even though they are foreign tissue that the body should, in theory, reject. A study in 1996 recorded women with fetal cells in their blood as many as 27 years after giving birth 13 ; another found that maternal cells remain in children up to adulthood 14 . This type of work has further blurred the sex divide, because it means that men often carry cells from their mothers, and women who have been pregnant with a male fetus can carry a smattering of its discarded cells.…”
Section: Cellular Sexmentioning
confidence: 99%
“…Most, if not all, pregnant women have fetal cells in their circulation (1). The persistence of these cells for decades after pregnancy has also been demonstrated (2). However, it remains unclear why fetal cells persist in some women, creating a microchimeric state, and not in others.…”
mentioning
confidence: 99%
“…Although male DNA was used as the measure of microchimerism, women with SSc who had sons were studied for T lymphocyte microchimerism without comparison with control women with sons. The absence of appropriate controls was notable in view of the earlier description by Bianchi et al of fetal microchimerism among T lymphocytes in healthy women (2). Subsequent studies confirmed that simple detection of fetal microchimerism is common among T lymphocytes (and also in monocytes, natural killer cells, and B cells) in both women with SSc and healthy women (13).…”
Section: Fetal Microchimerism In Sscmentioning
confidence: 94%